2009
DOI: 10.1016/j.ydbio.2009.07.023
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-A and Semaphorin3A: Modulators of vascular sympathetic innervation

Abstract: Sympathetic nerve activity regulates blood pressure by altering peripheral vascular resistance. Variations in vascular sympathetic innervation suggest that vascular-derived cues promote selective innervation of particular vessels during development. As axons extend towards peripheral targets, they migrate along arterial networks following gradients of guidance cues. Collective ratios of these gradients may determine whether axons grow towards and innervate vessels or continue past non-innervated vessels toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 64 publications
1
33
0
Order By: Relevance
“…It is also a mitogen for astroglia and Schwann cells in vitro [3,16]. Studies have shown that exogenous VEGF-A increases the number of processes of the sympathetic ganglia in explants [17] and promotes the growth of sympathetic axons from surgically denervated adult rats [18]. VEGF-A promotes the growth of axons, independently from its vascular role, through two receptors: either VEGFR2 [19] or neuropilin-1 (NRP1) [20].…”
Section: Resultsmentioning
confidence: 99%
“…It is also a mitogen for astroglia and Schwann cells in vitro [3,16]. Studies have shown that exogenous VEGF-A increases the number of processes of the sympathetic ganglia in explants [17] and promotes the growth of sympathetic axons from surgically denervated adult rats [18]. VEGF-A promotes the growth of axons, independently from its vascular role, through two receptors: either VEGFR2 [19] or neuropilin-1 (NRP1) [20].…”
Section: Resultsmentioning
confidence: 99%
“…Netrin-1 was not expressed in the heart, and cardiac innervation was normal in Ntn1 mutants. Interestingly, a growing body of evidence indicates that innervation of the heart and large arteries is regulated by other molecules, including NGF and the axon guidance molecule Sema3A and its receptor Nrp1 (41)(42)(43). Therefore, sympathetic innervation of cardiovascular targets may be regulated by specific combinations of guidance molecules: Sema3A/Nrp1 for the heart and large arteries and netrin/DCC for resistance arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, exogenous VEGF-A increases neurite outgrowth from sympathetic ganglion explants (Long et al, 2009) and promotes sympathetic axon growth for re-innervation of surgically denervated femoral arteries in adult rats (Marko and Damon, 2008). VEGF-A also promotes the sympathetic regulation of resistance arteries, as their constriction is reduced in response to cold stress in Vegfa delta/delta mice with low levels of endogenous VEGF-A (Storkebaum et al, 2010).…”
Section: Vegf-a In Axon Guidancementioning
confidence: 99%